2017
DOI: 10.1115/1.4037868
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Emissions Characteristics of Marine Diesel Engine Intake of Exhaust Gas of Lean Burn Gas Engine

Abstract: The need for reductions of nitrogen oxides (NOx), sulfur oxides (SOx), and carbon dioxide (CO2) emissions has been acknowledged on the global level. However, it is difficult to meet the strengthened emissions regulations by using the conventional marine diesel engines. Therefore, lean burn gas engines have been recently attracting attention in the maritime industry. Because they use natural gas as fuel and can simultaneously reduce both NOx and CO2 emissions. On the other hand, since methane is the main compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…However, interviewed experts and past studies suggest that maintaining the ideal performance conditions for these catalysts can be challenging during ship operations [70]. EGR systems and negative engine valve overlap mechanisms work by reusing the unburnt methane for the next engine combustion cycle, which would have otherwise been emitted through the exhaust valve [71,72]. The reuse of such exhaust gas streams reduces both NO x emissions and methane slip from marine dual-fuel engines [71].…”
Section: Technological Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…However, interviewed experts and past studies suggest that maintaining the ideal performance conditions for these catalysts can be challenging during ship operations [70]. EGR systems and negative engine valve overlap mechanisms work by reusing the unburnt methane for the next engine combustion cycle, which would have otherwise been emitted through the exhaust valve [71,72]. The reuse of such exhaust gas streams reduces both NO x emissions and methane slip from marine dual-fuel engines [71].…”
Section: Technological Measuresmentioning
confidence: 99%
“…EGR systems and negative engine valve overlap mechanisms work by reusing the unburnt methane for the next engine combustion cycle, which would have otherwise been emitted through the exhaust valve [71,72]. The reuse of such exhaust gas streams reduces both NO x emissions and methane slip from marine dual-fuel engines [71].…”
Section: Technological Measuresmentioning
confidence: 99%
“…The fuel composition is presented in Table 3, as described in the former data. 12 The test engine was not adjusted to suppress the THC emissions, including CH 4 emissions, at low engine loads.…”
Section: Catalyst Activity Test In Actual Exhaust Gasmentioning
confidence: 99%
“…11 Therefore, the authors have been investigating the suitable aftertreatment systems for marine power systems in the gas fuelled ships to reduce the methane slip. 12,13 A different approach to applying CH 4 oxidation catalysts as an aftertreatment for marine gas-engines is also expected as an aftertreatment system.…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have done a lot of research work on EGR and SCR technology. The effect of EGR on combustion and emission characteristics can be divided into thermal effect, dilution effect, , and chemical effect. , Research has shown that a lower level of NO x emissions can be achieved by using EGR and that the effect is very significant; moreover, EGR combined with cylinder bypass and exhaust gas bypass reduces NO x emissions . Meanwhile, the EGR rate also has a certain impact on soot emission, which decreases significantly with the EGR rate under different forms of EGR and excess air ratios .…”
Section: Introductionmentioning
confidence: 99%